Indígenas urbanos vida e ausência de direitos : estudo de caso do Povo Xavante em Barra do Garças - MT - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The original peoples of Brazil throughout the country's historical trajectory did not receive significant recognition, either from the State or from society, which overshadowed and repressed their culture. Their territories have always been targets of atta cks, causing dispersion and genocide of many ethnicities. Economic power, from the exploration of Pau Brasil, mining, coffee, rubber extraction, grain planting, cattle breeding, has always aspired and still aspired to Indigenous Lands. In the face of these attacks, the original peoples were hostage to the neglect and abandonment on the part of the Federal Government, since government actions such as public policies were not directed at the indigenous populations, as original peoples, but rather as peoples w ho hinder economic development. In this sense, in the 21st century, indigenous people are in a chaotic situation, where their lives and territory continue to be threatened and, as a result of these facts, many indigenous people are leaving their villages t o live in the city. The present research aimed to understand the socioeconomic and cultural situation of the Xavante people who live in the city of Barra do Garças MT. It is known that indigenous displacement to cities is a difficult decision for these peo ple who have specific ways of life in their territories. The research is qualitative, its methodology was case study and fieldwork, with interviews and photographic records being essential methodological procedures. The research revealed the dissatisfaction of the Xavante People with the public services offered by the governments: municipal, state and federal, as well as the prejudice of non Indians towards the Xavante, the precarious housing conditions and segregation of public spaces.
Indigenous urban life and the absence of rights : case study of the Xavante People in Barra do Garças - MT
Keywords: Povo Xavante; Cidade; Identidade; Abandono; Resistência; Xavante People; City; Identity; Abandonment; Resistance; GEOGRAFIA::GEOGRAFIA HUMANA